THE INFLUENCE OF LEADERSHIP, COMMUNICATION, AND SPIRITUALITY ON ORGANIZATIONAL PERFORMANCE: CASE STUDY AT SKG INDONESIA KARATE SCHOOL - Hendratmoko; Mutiarawati, Elisabeth Vita (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
The purpose of this study is to analyze the influence of leadership, communication, and spirituality variables on organizational performance. This study uses a qualitative approach by conducting in-depth interviews with five respondents. The five respondents are active karate practitioners who hold a black belt. The results of this study prove that the variables of leadership, communication, and spirituality have a significant influence on organizational performance. The role of the communication variable as a common moderator of the relationship between leadership and spirituality variables on performance and the spirituality variable as a partial moderator of the relationship between communication and leadership variables on performance.